2003
DOI: 10.1074/jbc.m308967200
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Sulfur Cluster N2 of the Escherichia coli NADH:Ubiquinone Oxidoreductase (Complex I) Is Located on Subunit NuoB

Abstract: The proton-pumping NADH:ubiquinone oxidoreductase, also called respiratory complex I, couples the transfer of electrons from NADH to ubiquinone with the translocation of protons across the membrane. One FMN and up to 9 iron-sulfur (Fe/S) clusters participate in the redox reaction. There is discussion that the EPR-detectable Fe/S cluster N2 is involved in proton pumping. However, the assignment of this cluster to a distinct subunit of the complex as well as the number of Fe/S clusters giving rise to the EPR sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 69 publications
0
54
1
Order By: Relevance
“…Because this length does not allow incorporation of the whole operon into expression vectors, a site-specific mutation is traditionally carried out by complementation of a cassette-inserted gene with a mutated gene in the expression plasmid (designated in trans complementation) (37)(38)(39)(40)(41)(42)(43). However, the in trans complementation procedure presents some problems when applied to a gene cluster.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because this length does not allow incorporation of the whole operon into expression vectors, a site-specific mutation is traditionally carried out by complementation of a cassette-inserted gene with a mutated gene in the expression plasmid (designated in trans complementation) (37)(38)(39)(40)(41)(42)(43). However, the in trans complementation procedure presents some problems when applied to a gene cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Another problem is that the mutated gene is under the control of a promoter in the expression plasmid, which often leads to overexpression of the mutated subunit. In mutation studies of the NDH-1 using the in trans complementation, it has been reported that the enzyme activities were significantly low (ϳ20% of the wild type cells) even when the unmutated gene was used (42,43,45). An alternative method of site-directed mutation is to introduce mutations directly in chromosomal DNA as detailed in this work (designated chromosomal DNA mutation, see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They may include NuoA, which has been suggested to interact with NuoB (33), or NuoH, which may contain a ubiquinone-binding site (4). It has been suggested that subunit NuoB coordinates iron-sulfur cluster N2 (34), which has a high pH-dependent midpoint potential and is, therefore, proposed to reduce ubiquinone and play a key role in proton translocation (4). The mobility of subunit NuoB, which we observed, would be consistent with such a role and may reflect movements of this subunit during the catalytic cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we are unable to attribute N4 specifically to 4Fe[I]1 or 4Fe[I]2 or to rule out the possibility that both clusters contribute. Point mutants of the Cys residues in E. coli NuoI have been created, but only one variant (C102A, where C102 is a ligand of 4Fe[I]2) was amenable to study by EPR, and the N4 signal remained clearly visible (48).…”
Section: Assigning Epr Signals To the Fes Clusters In Nuog Andmentioning
confidence: 99%